Colour and tissue differences in distribution of quercetin in Indian onions (Allium cepa) - Qureshi, A Aziz; Lawande, K E; Mani, Sibi; Patil, Vaishali B (The Indian Journal of Agricultural Sciences, 2012)
The above investigation revealed that quercetin content varied spatially in the bulb portions as well as in the rings of short-day Indian onions. It was high in top portion of bulb or in the outer rings. Dark coloured bulbs had greater amounts of quercetin in comparison to white bulbs. These findings would provide essential information for majority of people in India, South Asia and Gulf who consume onion in salads about the coloured bulbs that it contains more quercetin levels. Hence, consumption of coloured bulbs particularly the top portion or outer rings is more beneficial in meeting the dietary requirement of quercetin, which is an essential health compound.